2011
DOI: 10.2135/cropsci2010.12.0699
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Leaf Nitrogen in Corn from Digital Images

Abstract: Environmental concerns of nitrate pollution coupled with the cost of N fertilizers have led to increased interest in assessing plant N status. Our objective was to use a digital camera and image-analysis software to assess leaf N concentration in corn {Zea mays L.) leaves from the association between leaf N and green color of chlorophyll. In greenhouse experiments conducted at Fayetteville, AR, in 2008 and 2009, digital photographs of the uppermost collared leaf of 3-to 5-leaf corn plants grown over a range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 20 publications
5
43
0
1
Order By: Relevance
“…Two spectral indices were selected for analysis, the dark green color index (DGCI) and the triangular greenness index (TGI), because both indices are calculated with red, green, and blue bands (Karcher and Richardson, 2003;Rorie et al, 2011aRorie et al, , 2011bHunt et al, 2011Hunt et al, , 2013. The DGCI was calculated by first transforming R, G, and B values into hue, saturation, and brightness values: …”
Section: Image Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two spectral indices were selected for analysis, the dark green color index (DGCI) and the triangular greenness index (TGI), because both indices are calculated with red, green, and blue bands (Karcher and Richardson, 2003;Rorie et al, 2011aRorie et al, , 2011bHunt et al, 2011Hunt et al, , 2013. The DGCI was calculated by first transforming R, G, and B values into hue, saturation, and brightness values: …”
Section: Image Analysesmentioning
confidence: 99%
“…Videography and photography have become widespread for low-cost analysis of green leaf color (Spomer et al, 1988;Kawashima and Nakatani, 1998;Adamsen et al, 1999;Scharf and Lory, 2002;Karcher and Richardson, 2003;Dani et al, 2005;Rorie et al, 2011aRorie et al, , 2011b. Our hypothesis was that digital color photographs of leaves with the LCC could provide an objective, reproducible, and potentially automated method for determining LCC values in maize.…”
mentioning
confidence: 99%
“…The nitrogen content in the leaves can also be determined by analysing the distribution of colour components of the image of a single leaf or group of plants (Kawashima, Nakatan, 1998;Mercado-Luna et al, 2010;Rorie et al, 2011;Yuzhu et al, 2011;Wang et al, 2014). The aim of the study was to evaluate whether the concentration of nitrogen in apple trees leaves could be reliably estimated with an image analysis method using a flatbed scanner.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Normalized Green Red difference index (NGRDI) shows sensitivity to different chlorophyll concentration in leaves (Hunt et al, 2005). Rorie et al, (2011a;2011b) found that Dark Green Colour index (DGCI) have a close association with leaf N in corn. Furthermore, Hunt (2013) developed the Triangular Greenness Index (TGI) based on Vis bands for determining status of chlorophyll content in crops (R 2 = 0.85).…”
Section: Introductionmentioning
confidence: 99%